1997
DOI: 10.1017/s0266462300010059
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Cost-Effectiveness in Hip and Knee Replacements:A Prospective Study

Abstract: The extensive benefits of the total hip (THA) and knee (TKA) replacements are well documented, but surprisingly little is known about their economics. We assessed costs, cost-effectiveness (C/E), and patient-related C/E variances in THA and TKA from data on 276 THA and 176 TKA patients. Patients with primary arthrosis, primary operation, and total joint replacement were recruited from seven hospitals between March 1991 and June 1992. Their use of health and other welfare services together with health-related q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 36 publications
(11 reference statements)
5
71
0
7
Order By: Relevance
“…Cost-utility analysis: base case and sensitivity analyses (SA) varying the discount rate between 1% and 5%, using median values, and using the upper and lower values of the 95% confidence interval (CI) for the mean differences in treatment effectiveness (improvement in health-related quality of life) and costs. See Table 1 (Rissanen et al 1997). Thus, the method of using cost data that are readily available from the hospital accounting system instead of tediously collecting data from individual patients can be defended, and is in fact-in a trial involving several thousand patients-the only feasible way of acquiring reasonably reliable cost data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost-utility analysis: base case and sensitivity analyses (SA) varying the discount rate between 1% and 5%, using median values, and using the upper and lower values of the 95% confidence interval (CI) for the mean differences in treatment effectiveness (improvement in health-related quality of life) and costs. See Table 1 (Rissanen et al 1997). Thus, the method of using cost data that are readily available from the hospital accounting system instead of tediously collecting data from individual patients can be defended, and is in fact-in a trial involving several thousand patients-the only feasible way of acquiring reasonably reliable cost data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have suggested that total hip arthoplasty (THA) and total knee arthoplasty (TKA) are more cost-effective than many other healthcare interventions (Laupacis et al 1994, James et al 1996, Rissanen et al 1997, Garellick et al 1998, O'Shea et al 2002, Segal et al 2004. The estimates of cost-effectiveness, however, have usually been based on results of individual studies comparing only two or a few interventions at a time.…”
mentioning
confidence: 99%
“…First, ADL was classified into three categories (good, moderate or poor), thus building a new variable, coping ability in daily life (CADL), using the procedure described by Jylhä (1985) (c.f. Noro 1998Rissanen 1996). According to this procedure, CADL was classified as good if the client had no difficulties in any of the items in ADL.…”
Section: Instrumentsmentioning
confidence: 99%
“…Este estudio se centra en el empowerment o empoderamiento de los pacientes con OA durante el proceso quirúrgico de ATC y ATR, mediante actividades de información-educación. Se han escogido estas cirugías ya que influyen de manera notable en las actividades de la vida diaria de los pacientes y de sus familias, 27,28,29,30,31,32 y pueden ser apoyadas con información-educación de los pacientes. En el sistema nacional de salud, la demanda de tales intervenciones supera ampliamente la oferta, lo que da lugar a largas listas de espera.…”
unclassified
“…Este doble instrumento surge de las teorías sociales-psicológi-cas y constructivas aplicadas al empoderamiento de los pacientes a través de la educación (25,26). La ECPH/CRPH, fue creada originalmente en Finlandia, para pacientes con esclerosis múltiple(23), y más tarde, utilizada para pacientes quirúrgicos (20,(27)(28)(29)(30)(31).La validez y la fiabilidad han sido demostradas en los diversos estudios previos.La ECPH/CRPH permite evaluar las expectativas de conocimiento que tienen los pacientes antes de ingresar en el hospital (ECPH) y el conocimiento recibido durante la hospitalización en el momento del alta (CRPH) (19,23). El conocimiento se evalúa en 40 ítems divididos en 6 dimensiones: biofisiológica (preguntas de la 1 a la 8, sobre enfermedad, síntomas, pruebas, tratamientos y complicaciones), funcional (preguntas de la 9 a la 16 sobre movilidad, reposo, nutrición e higiene corporal), de experiencia (preguntas de la 17-19 sobre sentimientos y experiencias), ética (preguntas de la 20 a la 28 sobre derechos, deberes, participación en la toma de decisiones y confidencialidad), social (preguntas de la 29 a la 34 sobre cuidadores, personas de soporte y organizaciones de pacientes) y económica (preguntas de la 35 a la 40 sobre los costes).…”
unclassified